Comparative demography of commercially important species of coral grouper, Plectropomus leopardus and P. laevis , from Australia's great barrier reef and Coral Sea marine parks - Samuel D. Payet; Jake R. Lowe; Bruce D. Mapstone; Morgan S. Pratchett; Tane H. Sinclair‐Taylor; Brett M. Taylor; Peter A. Waldie; Hugo B. Harrison (Journal of Fish Biology, 2020)
Understanding the spatial and environmental variation in demographic processes of fisheries target species, such as coral grouper (Genus: Plectropomus ), is important for establishing effective management and conservation strategies. Herein we compare the demography of Plectropomus leopardus and P. laevis between Australia's Great Barrier Reef Marine Park (GBRMP), which has been subject to sustained and extensive fishing pressure, and the oceanic atolls of Australia's Coral Sea Marine Park (CSMP), where there is very limited fishing for reef fishes. Coral grouper length‐at‐age data from contemporary and historical otolith collections across 9.4 degrees of latitude showed little difference in lifetime growth between GBRMP and CSMP regions. Plectropomus laevis populations in GBRMP reefs had significantly higher rates of total mortality than populations in the CSMP. Mean maximum lengths and mean maximum ages of P. laevis were also smaller in the GBRMP than in the CSMP, even when considering populations sampled within GBRMP no‐take marine reserves (NTMRs). Plectropomus leopardus , individuals were on average smaller on fished reefs than NTMRs in the GBRMP, but all other aspects of demography were broadly similar between regions despite the negligible levels of fishing pressure in the CSMP. Similarities between regions in growth profiles and length‐at‐age comparisons of P. laevis and P. leopardus suggest that the environmental differences between the CSMP and the GBRMP may not have significant impacts on lifetime growth. Our results show that fishing may have influenced the demography of coral grouper on the GBR, particularly for the slower growing and longer lived species, P. laevis .

Integrated ecological–economic fisheries models—Evaluation, review and challenges for implementation - J Rasmus Nielsen; Eric Thunberg; Daniel S Holland; Jorn O Schmidt; Elizabeth A Fulton; Francois Bastardie; Andre E Punt; Icarus Allen; Heleen Bartelings; Michel Bertignac; Eckhard Bethke; Sieme Bossier; et al. (Fish and Fisheries, 2018)
Marine ecosystems evolve under many interconnected and area‐specific pressures. To fulfil society's intensifying and diversifying needs while ensuring ecologically sustainable development, more effective marine spatial planning and broader‐scope management of marine resources is necessary. Integrated ecological–economic fisheries models ( IEEFM s) of marine systems are needed to evaluate impacts and sustainability of potential management actions and understand, and anticipate ecological, economic and social dynamics at a range of scales from local to national and regional. To make these models most effective, it is important to determine how model characteristics and methods of communicating results influence the model implementation, the nature of the advice that can be provided and the impact on decisions taken by managers. This article presents a global review and comparative evaluation of 35 IEEFM s applied to marine fisheries and marine ecosystem resources to identify the characteristics that determine their usefulness, effectiveness and implementation. The focus is on fully integrated models that allow for feedbacks between ecological and human processes although not all the models reviewed achieve that. Modellers must invest more time to make models user friendly and to participate in management fora where models and model results can be explained and discussed. Such involvement is beneficial to all parties, leading to improvement of mo‐dels and more effective implementation of advice, but demands substantial resources which must be built into the governance process. It takes time to develop effective processes for using IEEFM s requiring a long‐term commitment to integrating multidisciplinary modelling advice into management decision‐making.

Effects of region, demography, and protection from fishing on batch fecundity of common coral trout (Plectropomus leopardus) - Alex B. Carter; Campbell R. Davies; Bruce D. Mapstone; Garry R. Russ; Andrew J. Tobin; Ashley J. Williams (Coral Reefs, 2014)

Establishing Representative No‐Take Areas in the Great Barrier Reef: Large‐Scale Implementation of Theory on Marine Protected Areas - LEANNE FERNANDES; JON DAY; ADAM LEWIS; SUZANNE SLEGERS; BRIGID KERRIGAN; DAN BREEN; DARREN CAMERON; BELINDA JAGO; JAMES HALL; DAVE LOWE; JAMES INNES; JOHN TANZER; et al. (Conservation Biology, 2005)
The Great Barrier Reef Marine Park, an area almost the size of Japan, has a new network of no‐take areas that significantly improves the protection of biodiversity. The new marine park zoning implements, in a quantitative manner, many of the theoretical design principles discussed in the literature. For example, the new network of no‐take areas has at least 20% protection per “bioregion,” minimum levels of protection for all known habitats and special or unique features, and minimum sizes for no‐take areas of at least 10 or 20 km across at the smallest diameter. Overall, more than 33% of the Great Barrier Reef Marine Park is now in no‐take areas (previously 4.5%). The steps taken leading to this outcome were to clarify to the interested public why the existing level of protection was inadequate; detail the conservation objectives of establishing new no‐take areas; work with relevant and independent experts to define, and contribute to, the best scientific process to deliver on the objectives; describe the biodiversity (e.g., map bioregions); define operational principles needed to achieve the objectives; invite community input on all of the above; gather and layer the data gathered in round‐table discussions; report the degree of achievement of principles for various options of no‐take areas; and determine how to address negative impacts. Some of the key success factors in this case have global relevance and include focusing initial communication on the problem to be addressed; applying the precautionary principle; using independent experts; facilitating input to decision making; conducting extensive and participatory consultation; having an existing marine park that encompassed much of the ecosystem; having legislative power under federal law; developing high‐level support; ensuring agency priority and ownership; and being able to address the issue of displaced fishers.